Contemporary Buddha’s teaching as a Path to Liberation - Ružica Čičak-Chand (In Medias Res, 2018)
Buddhism is essentially a teaching about liberation – from suffering, ignorance and rebirth. Knowledge of ‘the way things really are’ is considered to be vital in bringing about this emancipation. Therein, Buddhist atheistic nature, theory about non-existence of the self, of the essence (anattā-vada), the law of impermanence and dependent origination (pațica-samuppādo ), its discovery of relativity brings it close to science, while the methodology of Buddhism – ethics and meditation – that is, its practice-based non-religious essence is one of the great resources in developing understanding of human subjectivity. Precisely in these essential teachings, Buddhism remains equally modern and accessible today, and at this aspect of its legacy we will try to point out, though fragmentarily.